Representations of depression and schizophrenia in the community: The role of illness and risk perceptions on help-seeking intentions - Neto, David Dias; Figueiras, Maria João; Sebastião, Rita (Frontiers in Psychology, 2022)
Objective. Illness perceptions (IP) are important in understanding human reactions to illnesses – including mental health disorders. They influence risk perceptions and several variables relevant for adjustment to a disorder, treatment seeking and health outcomes. The present study sought to compare IP, risk perception and help-seeking intention for depression and schizophrenia in a community sample and to assess the mediating role of risk perception in the relationship between IP and help-seeking intention. Methods. 380 adults participated in this study and filled self-report measures of illness perceptions, risk perceptions and help-seeking intention. The previous diagnosis of depression was used to control the comparisons between the two disorders. A Structural Equation Model (SEM) was used to test the mediation relationship. Results. Perceived consequences, expected timeline, lack of personal control and symptom identity were higher for schizophrenia, while lack of treatment control and concern were higher for depression. An interaction occurred with a previous diagnosis of depression for several dimensions of IPs. Concerning the SEM, a valid model was obtained for depression - explaining 15.5% of help-seeking intention – but not for schizophrenia. Conclusions. The results show that the general population represent depression and schizophrenia differently. These representations are influenced by having experienced depression, and that illness and risk perceptions contribute to explaining the intention to seek help. Considering these illness representations makes it possible to understand the general population’s emotional and cognitive reactions to mental health disorders.